IMPLEMENTATION OF A QUR’ANIC THERAPY APPROACH FOR THE PSYCHOLOGICAL WELL-BEING OF STUDENTS AT SMAN 3 PASURUAN CITY - Rochmatus Saidah; Atika Robiatul Adawiyah; Siti Rofiqoh At-Thobibi (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This study aims to analyze the implementation of a Qur’anic therapy approach in improving the psychological well-being of students at SMAN 3 Pasuruan City. The research is grounded in the growing concern over students’ mental health issues, such as stress, anxiety, and emotional instability, which require integrative and value-based interventions. This study employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation involving teachers, school counselors, and students. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the implementation of the Qur’anic therapy approach is carried out through structured activities such as Qur’an recitation (tilawah), memorization (tahfidz), reflection on meanings (tadabbur), and spiritual guidance sessions. These activities are integrated into both formal and non-formal school programs. The results indicate that the approach contributes positively to students’ psychological well-being, including increased emotional control, reduced anxiety levels, enhanced self-awareness, and strengthened spiritual resilience. Supporting factors include teacher commitment, a conducive religious environment, and institutional support, while inhibiting factors involve limited time allocation and varying levels of student engagement. In conclusion, the Qur’anic therapy approach serves as an effective alternative in fostering students’ psychological well-being through holistic integration of spiritual and psychological dimensions. This study recommends the development of more systematic program designs and broader implementation in educational institutions.